Konstitusionalitas Penerapan Mekanisme Omnibus Law dalam Pembentukan Undang-Undang Di Indonesia - Simabura, Charles; Fajri, M. Nurul (UI Scholars Hub, 2022)
This paper intends to describe how the omnibus law mechanism applied in lawmaking in Indonesia. Look at the 2020 priority national legislation program, which includes four draft bills that formed using the omnibus law mechanism. The omnibus law is a new mechanism in the lawmaking process in Indonesia. Because this mechanism not contained in Law Number 12 of 2011 concerning the Formation of Laws and Regulations as amended by Law Number 15 of 2019 concerning Amendments to Law Number 12 of 2011 concerning the Formation of Laws and Regulations. With this, the first thing that must answer is the question of the constitutionality of its application. Therefore the omnibus law is a law that formed to change or cancel the various norms that existed in many Laws that had previously been in effect. The aim is to be able to provide policy recommendations on the application of the omnibus law mechanism in the formation of laws in Indonesia. The research method used in this paper is prescriptive-descriptive legal research with a normative juridical approach.